Distribution of Calbindin-D28k in the cerebellum of Martes foina - Short communication - Timurkaan, Sema; Karan, Meryem; Atalar, Ömer (My University, 2006)
The localization of Calbindin in the cerebellum of beech marten (Martes foina Erxleben, 1777) has been investigated immunohistochemically using an antiserum raised against the Calbindin-D28k from chicken duodenum. Calbindin-D28k is an intracellular protein with high affinity for calcium. In the marten's cerebellum, positive staining was found in only Purkinje cells. Immunoreactive Calbindin-D28k is detected in all parts of the neuron, i.e. cell, soma, proximal processes, axons and terminals.
Keywords: Beech marten; Calbindin-D28k; Cerebellum; Immunohistochemistry; Martes foina; Stone marten